-7=-4+w/3

Simple and best practice solution for -7=-4+w/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7=-4+w/3 equation:



-7=-4+w/3
We move all terms to the left:
-7-(-4+w/3)=0
We add all the numbers together, and all the variables
-(w/3-4)-7=0
We get rid of parentheses
-w/3+4-7=0
We multiply all the terms by the denominator
-w+4*3-7*3=0
We add all the numbers together, and all the variables
-1w-9=0
We move all terms containing w to the left, all other terms to the right
-w=9
w=9/-1
w=-9

You can always share this solution

See similar equations:

| 5n=13-8n-9 | | 4^x+1x8^3x-1=256 | | 500x+4500=9500 | | -x=2.8(3x+5)-2.6x | | | | | | -3x+7+x=-3 | | 9n-9=18 | | 3x+12=x/2-8 | | X^2-4y^2=24 | | 15x-1.5=24 | | 9m+26=5m+3 | | x^2+12x-51=0 | | 2x-16=x+44 | | 3y+4(7-2y)-6(y+14)=-1-(y+5) | | (6y•2)=-5•6y-6+174 | | -(1-5x)+6=10+5x | | F4(w-5)-4=-3(-7w+4)-7w | | 11x-5=8x-6 | | -4w+10=-2(w-7) | | 3/10=10x | | 4(w-4)-8w=-8 | | 4(5+8d)D=84 | | 2-6(1-x)+x=4(2x-1)-x | | 17x-3=-43 | | 80-2x=30x= | | (10x+6)(6x+4)=90 | | (a+2)*(a+3)=3 | | -6=(5x-12)/3 | | 2a+1=10 | | (2x-1)(x+17)=0 | | 1+7p+p=1 | | 3(m+5)=12 |

Equations solver categories